2017
DOI: 10.1016/s1474-4422(17)30114-x
|View full text |Cite|
|
Sign up to set email alerts
|

Individualised prediction model of seizure recurrence and long-term outcomes after withdrawal of antiepileptic drugs in seizure-free patients: a systematic review and individual participant data meta-analysis

Abstract: Background. People with epilepsy who became seizure-free while taking antiepileptic drugs (AEDs) may

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
296
5
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(333 citation statements)
references
References 33 publications
20
296
5
12
Order By: Relevance
“…In human medicine, focal seizures are associated with seizure recurrence not only in PEE but also in other types of epilepsies . In this study, 42% of dogs experienced both generalized and focal seizures and 21% had only focal seizures.…”
Section: Discussionmentioning
confidence: 53%
“…In human medicine, focal seizures are associated with seizure recurrence not only in PEE but also in other types of epilepsies . In this study, 42% of dogs experienced both generalized and focal seizures and 21% had only focal seizures.…”
Section: Discussionmentioning
confidence: 53%
“…It is important to emphasize that our study focused on patients with NOSE; thus, it is difficult to compare our results to most other studies, which investigated both pediatric and adult populations with and without a previous history of epilepsy, with and without SE. Among these studies, seizure recurrence in the setting of ASD weaning ranged from 12% to 66% . One study found an average recurrence rate of one‐third; however, there was no difference in long‐term outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Once seizure control is achieved in NOSE, patients may be discharged on multiple ASDs, which are medications that carry a high burden of side effects and psychosocial implications for patients . Successful weaning from ASDs in the inpatient setting has been shown, as well as in patients with epilepsy who have been seizure‐free for prolonged periods of time in the outpatient setting, but there is a paucity of data on the safety of discontinuing ASDs in NOSE after hospital discharge. There is a specific reluctance to wean patients off of barbiturate medications due to the possibility for seizure recurrence during withdrawal .…”
Section: Introductionmentioning
confidence: 99%
“…25 For diseases of the brain too, the ability to predict better (or worse) outcomes has been achieved by collating multiple markers, with higher numbers of markers performing better. [26][27][28][29] This strategy might be effective in psychiatry also. 30 Endophenotypes constructed from multiple social, clinical and brain volumetric alterations identified subgroups of patients that crossed diagnoses (n = 1872).…”
Section: What Next?mentioning
confidence: 99%